Hubungan antara Faktor Eksternal dan Internal selama Pembelajaran Daring pada Siswa Sekolah Menengah - Ahmad Kamal Sudrajat; Dwi Arianita Wulan Sari; Dita Purwinda Anggrella (SAP (Susunan Artikel Pendidikan), 2023)
External factors are thought to have a relationship with internal factors in the learning process of secondary students. However, there is still little research conducted to determine the relationship between the two factors. This research was conducted to determine the relationship between external factors and internal factors in online learning for high school students. Data were obtained by distributing questionnaires to high school students using the snowball technique. Data was collected from June 2021 to July 2021, and 513 responses were obtained. The data obtained was analyzed using descriptive and inferential statistics. The results of this study indicate that gender has a relationship with independent learning, environmental management, and student task strategies. The student's school level is related to learning readiness, learning control, and student learning motivation. Gadget ownership status is correlated with students' self-directed learning. While the type of internet access has nothing to do with any factor. This research will help determine the conditions and development of students during online learning. In addition, various parties can use it to improve the quality of online learning among children.